2003
DOI: 10.1093/bioinformatics/btg114
|View full text |Cite
|
Sign up to set email alerts
|

GeneMerge—post-genomic analysis, data mining, and hypothesis testing

Abstract: GeneMerge is available free of charge for academic use over the web and for download from: http://www.oeb.harvard.edu/hartl/lab/publications/GeneMerge.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
204
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(208 citation statements)
references
References 12 publications
(1 reference statement)
1
204
0
1
Order By: Relevance
“…A manual analysis of the computation-derived candidates with known identity (18/29) showed that they clustered in six function groups: 1) chromatin structure, 2) transcription/DNA-binding, 3) adhession/ intercellular junction, 4) Ion-channels, 5) signal transduction, and 6) protein transport/ endoplastic reticulum (Table 2). Analysis with a web-based program GeneMerger [33] revealed similar enrichment (2-5 fold) in GO terms, which were statistically significant (see Supplementary Materials, S1), but the classification was not as precise as the manually built list. This result prompted us to compare the computation-derived basonuclin target genes with a list of genes perturbed by basonuclin-deficiency in mouse oocytes.…”
Section: Pathways Perturbed By Basonuclin-deficiency and The Basonuclmentioning
confidence: 99%
“…A manual analysis of the computation-derived candidates with known identity (18/29) showed that they clustered in six function groups: 1) chromatin structure, 2) transcription/DNA-binding, 3) adhession/ intercellular junction, 4) Ion-channels, 5) signal transduction, and 6) protein transport/ endoplastic reticulum (Table 2). Analysis with a web-based program GeneMerger [33] revealed similar enrichment (2-5 fold) in GO terms, which were statistically significant (see Supplementary Materials, S1), but the classification was not as precise as the manually built list. This result prompted us to compare the computation-derived basonuclin target genes with a list of genes perturbed by basonuclin-deficiency in mouse oocytes.…”
Section: Pathways Perturbed By Basonuclin-deficiency and The Basonuclmentioning
confidence: 99%
“…Specifically, our studies identify a subset of DLBCLs, the BCR tumors, in which BCL6 plays a critical biological role. The BCR consensus cluster designation was more accurate in predicting BPI sensitivity than Enrichment was evaluated using the GeneMerge program (18), which compares the frequency of GO categories represented in the nonredundant list of SwissProt/TrEMBL accession nos. of BCL6 target genes (n ϭ 418) versus the global frequency of GO categories in the population gene file [19,168 nonredundant SwissProt/TrEMBL accession nos.…”
Section: Bcl6 Actively Represses Its Target Genes In Bcr But Not Oxphosmentioning
confidence: 99%
“…GO enrichment analysis was carried out with GO biological process terms, and obtained P values were corrected for multiple-hypothesis testing by false-discovery rate (FDR) (24,25). P values (E scores) for GO term overrepresentation in the BCL6 target genes were obtained using the hypergeometric distribution (18,29). The hypergeometric distribution quantifies the overrepresentation of a given GO term in a sample of a specific size that is drawn from a larger population (18).…”
Section: Bcl6 Actively Represses Its Target Genes In Bcr But Not Oxphosmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible formation of HSF2-binding clusters was studied through the chromosomal distribution of target genes by using the GeneMerge analysis tool (18). To our surprise, a profound accumulation of HSF2 targets was detected on the Y chromosome, in comparison to the total amount of promoters per chromosome on the microarray (Table 1).…”
mentioning
confidence: 98%